2016
DOI: 10.4103/0973-029x.190906
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog in oral squamous cell carcinoma: An immunohistochemical study

Abstract: Background:Recent studies have revealed the involvement of hedgehog (Hh) signaling component in proliferation and invasive behavior of many carcinomas.Aim:This study aims to identify the expression of sonic Hh (SHH) protein of SHH pathway in oral epithelial dysplasia and oral squamous cell carcinoma (OSCC) using SHH (H-160) (Santa Cruz, sc-9042) which could have therapeutic implication in future.Materials and Methods:A total of 250 cases comprising 50 normal oral mucosa, 50 cases of oral epithelial dysplasia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
5
12
0
Order By: Relevance
“…Three Hedgehog homologs are present in mammals: Desert (DHH), Indian (IHH) and Sonic (SHH) 160 . Immunohistochemical results show that SHH signaling molecules are highly expressed in OSCC and considered as a potential target in oral cancer therapy 161,162 . In addition, SHH signaling is a potential promotor of OSCC associated with bone destruction 163,164 .…”
Section: Functional Regulatory Network Of Emt In Osccmentioning
confidence: 99%
“…Three Hedgehog homologs are present in mammals: Desert (DHH), Indian (IHH) and Sonic (SHH) 160 . Immunohistochemical results show that SHH signaling molecules are highly expressed in OSCC and considered as a potential target in oral cancer therapy 161,162 . In addition, SHH signaling is a potential promotor of OSCC associated with bone destruction 163,164 .…”
Section: Functional Regulatory Network Of Emt In Osccmentioning
confidence: 99%
“…Recently, several SHH-signaling proteins were also found overexpressed in OSCC patients. For example, SHH was highly expressed in OSCC and appeared in the cytoplasm of epithelial cells in immunohistochemical analyses [ 59 ]. Both SHH and GLI family zinc finger 1 (glioma-associated oncogene homolog 1; GLI1) are notably upregulated in 74 OSCC samples of immunohistochemical analyses.…”
Section: Shh Signaling and Oral Cancermentioning
confidence: 99%
“…Mutations in HH-pathways have been found in basal cell carcinoma, medulloblastoma, and rhabdomyosarcoma, and normally correlate with an hyperactivation of the pathway. Recent studies on protein expression showed that SHH signaling components are highly expressed in OSCC compared to normal tissue, with a restricted positive pattern in epithelial cells [160,161,162,163].…”
Section: Introductionmentioning
confidence: 99%